(untitled) (Research, Society and Development, 2022)
The objective of this work was to evaluate the impact of an educational campaign in reducing the waste of enteral diet in a Hospital. This is a descriptive, retrospective research with a quantitative approach. The knowledge of employees (nurses, nursing technicians and residents) participating in the “Campaign for the Quality of Enteral Nutrition” developed by the clinical nutrition area of the University Hospital was investigated, with the production of educational activities on Enteral Nutrition (EN). To verify the impact of the intervention on the quality indicators of enteral diet, the percentage of waste was evaluated, by recording the volume filled and not administered (L) / volume distributed (L) x 100, carried out in three different periods. 46 professionals were evaluated. Of the total, 80% said they consider EN important in the patient’s recovery, 43% consider having good knowledge about EN, 17% consider having some difficulty in handling EN equipment and 13% consider having difficulty receiving EN and ensuring its conservation. For the variable volume discarded, there was a significant difference compared to the periods “During” (p=0.044) and “After” (p=0.048). The average percentage of waste decreased from 0.48% to 0.15%. The main reasons related to waste were fasting for exams and procedures (44.4%), accidental removal of the tube (23.8%), death (9.5%) and hospital discharge (5.9%). The educational intervention triggered positive responses regarding the reduction of wasted diets.